Short-term complications of implant-supported and combined tooth-implant-supported fixed dental prostheses - Rammelsberg, Peter; Schwarz, Stefanie; Schroeder, Christin; Lorenzo Bermejo, Justo; Gabbert, Olaf (Clinical oral implants research, 2013)
Objective The objective of this clinical study was to evaluate survival and incidence of complications for metal-ceramic and all-ceramic implant-supported fixed dental prostheses (FDPs) and tooth-implant-supported FDPs. Material and methods One-hundred and sixty-six FDPs placed in 132 patients from a prospective study were selected for this retrospective analysis. Included were 91 conventional implant-supported FDPs with implant support on both extremities, 27 implant-supported cantilever FDPs, and 48 tooth-implant-supported FDPs. All restorations were veneered with ceramic. Twenty-six FDPs had a zirconia framework and 140 had a metal framework. Kaplan-Meier analysis was performed to estimate FDP success defined as complication-free survival and the Cox regression model was used to isolate risk factors for the most frequent complications. Results Within a median follow-up of 1 year and 2 months, three failures were caused by a failed implant (n = 2) and by extended chipping of the veneer (n = 1). In contrast with this low incidence of failure was a high incidence of complications including chipping (n = 29), loss of retention (n = 35), and abutment fractures (n = 2). Multivariate survival analysis revealed a significantly greater incidence of chipping for males and a tendency to increased incidence of chipping for zirconia-based FDPs. The incidence of loss of retention tended to be less for tooth-implant-supported FDPs, for which semi-permanent cement was the only significant risk factor, with a hazard ratio of almost 5. Conclusions As chipping of the ceramic veneer was the most frequent complication leading to substantial aftercare, improvements of ceramic veneers are desirable for zirconia-based and metal-based FDPs.
First published: 09 May 2012
Gesehen am 14.12.2021